Assessment of the potential reactivity of granitic rocks — Petrography and expansion tests. (August 2016) - Ramos, Violeta; Fernandes, Isabel; Santos Silva, António; Soares, Dora; Fournier, Benoit; Leal, Sara; Noronha, Fernando
Abstract: Granite is one of the most commonly employed materials in the production of aggregates for concrete, and represents 40% of the total volume of aggregates produced in Portugal. This type of rock is traditionally considered as slowly/late reactive or even non-reactive to alkalis. However, a number of cases of damaged concrete structures in Portugal, due to alkali–silica reaction, have been related to granitic aggregates. A research program has been developed in order to define the best test method for evaluating the potential alkali-reactivity of granitic rocks. The present study involved thirteen granites collected from different quarries. The tests carried out included: petrographic examination of the aggregate, as well as mortar and concrete expansion tests. It was concluded that the content of microcrystalline quartz correlates better with the results of concrete prism expansion tests than with the mortar-bar expansion test.